Correction: Surface-based fMRI-driven diffusion tractography in the presence of significant brain pathology: A study linking structure and function in cerebral palsy (PLoS ONE (2016) 11:8 (e0159540) DOI: 10.1371/journal.pone.0159540) - Reid, L.; Cunnington, R.; Boyd, Roslyn; Rose, S. (Public Library of Science, 2016)
Fig 7 appears incorrectly in the published article. Please see the correct Fig 7 and its caption here